A Case of Traumatic Choroidopathy With Subretinal Fluid. (March 2021) - Mishra, Kapil; Iftikhar, Mustafa; Channa, Roomasa
Purpose: We report a unique case of blunt ocular trauma with subretinal fluid (SRF), presumed to be traumatic choroidopathy as evidenced by multimodal imaging. Methods: A case report is presented. Results: A 22-year-old woman involved in a motor vehicle accident presented 1 day later to our emergency department with blurred vision in the left eye. Visual acuity was 20/40, significant SRF was present throughout the macula, and fluorescein angiography showed diffuse pooling and leakage. There were no retinal tears or intraocular inflammation. Indocyanine green angiography performed a week later showed patchy hypofluorescence in the affected area. One month later, visual acuity had improved to 20/20 and the SRF and the hypofluorescence on indocyanine green angiography had resolved. Conclusions: Subfoveal collection of SRF may be a cause of decreased vision following blunt ocular trauma. We hypothesize that in our case choroidal hypoperfusion and retinal pigment epithelial dysfunction contributed to the SRF collection.